Biennial Pattern of Rotavirus Gastroenteritis in The Netherlands and a Shifting Age Distribution After a Low Rotavirus Season, 2010–2016. Issue 9 (September 2018) - Verberk, Janneke D. M.; Pijnacker, Roan; Bruijning-Verhagen, Patricia; Franz, Eelco; Vennema, Harry; Hooiveld, Mariëtte; Hahné, Susan J. M.; de Melker, Hester E.
Abstract : A hyperendemic rotavirus season was expected after a low-endemic 2014 season in the Netherlands. Rotavirus detections were however similar in 2015 and lower in 2016 compared with 2010–2013. Gastroenteritis consultation rates were also similar in 2015, but the age distribution shifted to older children because of an accumulation of noninfected children. Results indicate a possible shift to a biennial rotavirus pattern.